-0.7-3(3-5.9q)=-5+15q

Simple and best practice solution for -0.7-3(3-5.9q)=-5+15q equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -0.7-3(3-5.9q)=-5+15q equation:


Simplifying
-0.7 + -3(3 + -5.9q) = -5 + 15q
-0.7 + (3 * -3 + -5.9q * -3) = -5 + 15q
-0.7 + (-9 + 17.7q) = -5 + 15q

Combine like terms: -0.7 + -9 = -9.7
-9.7 + 17.7q = -5 + 15q

Solving
-9.7 + 17.7q = -5 + 15q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-15q' to each side of the equation.
-9.7 + 17.7q + -15q = -5 + 15q + -15q

Combine like terms: 17.7q + -15q = 2.7q
-9.7 + 2.7q = -5 + 15q + -15q

Combine like terms: 15q + -15q = 0
-9.7 + 2.7q = -5 + 0
-9.7 + 2.7q = -5

Add '9.7' to each side of the equation.
-9.7 + 9.7 + 2.7q = -5 + 9.7

Combine like terms: -9.7 + 9.7 = 0.0
0.0 + 2.7q = -5 + 9.7
2.7q = -5 + 9.7

Combine like terms: -5 + 9.7 = 4.7
2.7q = 4.7

Divide each side by '2.7'.
q = 1.740740741

Simplifying
q = 1.740740741

See similar equations:

| 4x-29=105 | | 15-2(y-3)=6(2y+5)-5y | | 120cu=LWH | | 2.9(2x-2)+0.5x= | | (3y+4)2=28 | | 4x-3x-6=7 | | a-(a*.3)=30000 | | 4x-1=3x+1.5 | | 9x^2-30x+25+25=0 | | 19x^8-13x^6+3x^5= | | x+1x+16x=180 | | 5x-7=8x+77 | | 5x^2+20x+30= | | 23+4x=12 | | 0.5(x-12)+0.2(x+7)=0.3x+3.4 | | 10x-4x=19-7 | | (2w+1)(5-w)=0 | | 0=16t-29t-6 | | 2(u+1)+4u=(2u-1)+8 | | 6x+12=10y | | -2(8y-6)+4y=-2(y+1) | | 2x-21=x-91 | | .25(8x-12)=6(.33x-.5)+4 | | (1-6t)(1+2t^2)= | | y-(3y+7)= | | x+98+8=-56 | | 6f+3f+3+6=180 | | (h+4)(h+3)(h)=126 | | 7(u-2)-7=-2(-9u+3)-u | | x=2t^3-9t^2+12 | | h^3+7h^2+12h=126 | | 5m+4+2m=1 |

Equations solver categories